Are facemasks a priority for all staff in theatre to prevent surgical site infections during shortages of supply? A systematic review and meta-analysis. Issue 5 (October 2021) - Marson, Ben A.; Craxford, Simon; Valdes, Ana M.; Ollivere, Benjamin J.
Abstract: Background: The provision of facemasks must be prioritised when supplies are interrupted. These include supplies to operating rooms. The aim of this review is to evaluate the available evidence to determine the relative priority for the provision of facemasks in operating rooms to prevent surgical site infection. Methods: A systematic search of OVID Medline, Embase & Cochrane Central was completed. Candidate full-text articles were identified and analysed by two reviewers who also assessed risk of bias. Findings: Six studies were identified that described infections with and without facemask usage. The pooled effect of not wearing facemasks was a risk ratio for infection of 0.77 (0.62–0.97) in favour of not wearing masks. Only one case-controlled study evaluated facemask usage in implant surgery and demonstrated an odds ratio for developing infection of 3.34 (95% CI 1.94–5.74) if facemasks were not worn by the operating surgeon. Four studies collected microbiological cultures during periods in surgery with or without facemasks. Two demonstrated an increase in colony forming units in surgery where the wound was directly below the surgeon. One study showed equivocal results when masks were worn, and one was terminated early limiting interpretation. Conclusion: The use of facemasks by scrubbed staff during implant surgery should be mandatory to prevent infection. We recommend the use of facemasks by all scrubbed staff during other forms of surgery to protect the patient and staff, but the supporting evidence is weak. There is insufficient evidence to show that non-scrubbed staff must wear masks during surgery. Highlights: There are seven studies evaluating the impact of facemasks on bacterial infection. The benefits of facemasks in reducing bacterial infection is unclear. Facemasks should be worn to prevent surgical site infection in implant surgery.